Images, rituel sacrificiel et pouvoir dans le monde romain - Valérie Huet (Pallas, 2019)
I propose a synthesis of our knowledge on sacrificial images in the Roman world, focusing on those coming from Rome and Italy and displaying « traditional » religion. I offer a selected historiography of the subject, starting with the main contribution of the book written by Ines Scott Ryberg in 1955, concluding with the discussion of some theories, those of Richard Gordon and Jaś Elsner on sacrificial images and their relationships with power and cult, then that of Emmanuel Mayer that raises a number of questions on the role of the emperor in the elaboration of the images on which he is represented.